Simulasi Konsumsi Energi Bangunan Berbentuk Dome Sebagai Upaya Optimalisasi Desain - Nova Purnama Lisa; Syafiqah Qamar (Jurnal Serambi Engineering, 2022)
The shape of the building, if projected against the sun's orientation, can provide shading and response to solar radiation because the shape of building and layout of the building provides a warming and cooling impact. The design of the shape of the building at the resort also pays attention to the orientation and functioning of the building related to its effect on the energy consumption produced. In the design process, many energy costs are found to be very expensive, therefore it takes efforts to control and save energy in buildings from the design stage of shape and pattern of space. The need for building energy is mostly used for air conditioning and lighting, both of which are filled by light and the orientation of the sun that enters the building both through the building sheath. So the shape and position of the building sheath are very dependent on the basic shape and orientation of the building. The problem in this study, the basic shape design of dome-shaped resort buildings responds to the increase and decrease in energy use in the resulting buildings per year. The study aims to find out how much energy efficiency a dome-shaped building produces if it is built and declared viable or not for residence by the user. The variable used is Annual Energy CO2, Annual Energy Cost, and Annual Energy Use. This study uses experimental methods of modeling simulation through software plug-in Sefaira. The result of the Sefaira simulation shows that to get value. KWH/year as much as 71 kWh/m2/yr, by the target ASHRAE 90.1-2019. The results showed that the dome-shaped resort building belongs to the category of not low energy against the challenge UIE 2030 38 kWh/m2/yr, based on the amount of energy consumption produced.